2014
DOI: 10.1371/journal.pone.0090921
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Down of CD44 Regulates Endothelial Cell Differentiation via NFκB-Mediated Chemokine Production

Abstract: A striking feature of microvascular endothelial cells is their capacity to fuse and differentiate into tubular structures when grown in three-dimensional (3D) extracellular matrices, in collagen or Matrigel, mimicking the in vivo blood vessel formation. In this study we demonstrate that human telomerase-immortalised foreskin microvascular endothelial (TIME) cells express high levels of the hyaluronan receptor CD44 and the hyaluronidase HYAL2. Knock-down of CD44 or HYAL2 resulted in an inability of TIME cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 73 publications
(113 reference statements)
1
44
0
1
Order By: Relevance
“…35, 44, 45 However, in endothelial cells, knocking down CD44 had no effect on ERK1/2. 46 Similarly, in the current studies, CD44 had no effect on ERK1/2 activation. Our results showed a spectrum of staining for both CD44/β-gal and for pERK.…”
Section: Discussionsupporting
confidence: 71%
“…35, 44, 45 However, in endothelial cells, knocking down CD44 had no effect on ERK1/2. 46 Similarly, in the current studies, CD44 had no effect on ERK1/2 activation. Our results showed a spectrum of staining for both CD44/β-gal and for pERK.…”
Section: Discussionsupporting
confidence: 71%
“…Wang et al (70) reported that CD44 regulates EC proliferation and tubule formation induced by HA fragments in HUVEC. In telomerase-immortalized foreskin microvascular ECs, Olofsson et al (71) demonstrated that inhibiting CD44 or Hyal2 expression prevented tubular network formation in three-dimensional matrices. In addition, CD44 and TLR4 can be physically associated in a signaling complex after exposure to HA, and endothelial TLR4 regulates certain responses to HA fragments (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…Wang, Cao, et al (2011) reported that CD44 regulates EC proliferation and tubule formation induced by HA fragments in HUVECs. In telomerase-immortalized foreskin microvascular EC, Olofsson, Porsch, and Heldin (2014) demonstrated that inhibiting CD44 or Hyal2 expression prevented tubular network formation in 3D matrices. In addition, CD44 and TLR4 can be physically associated in a signaling complex following exposure to HA and endothelial TLR4 regulates certain responses to HA fragments (Taylor et al, 2004, 2007).…”
Section: Ha Regulation Of Endothelial Barrier Function During Tumomentioning
confidence: 98%